Immobilization of heavy metals in contaminated soil after mining activity by using biochar and other industrial by-products the significant role of minerals on the biochar surfaces - Dang, Van Minh (Environmental technology, 2019)
Heavy metal contamination of crop lands surrounding mines in North Vietnam is a major environmental issue for both farmers and the population as a whole. Technology for the production of biochar at a village and household level has been successfully introduced into Vietnamese villages. This study was undertaken to determine if rice straw biochar produced in simple drum ovens could remediate contaminated land. Tests were also carried out to determine if biochar and apatite mixed together could be more effective than biochar alone. Incubation trials were carried out over 90 days in pots to determine the total changes in exchangeable Cd, Pb and Zn. Detailed tests were carried out to determine the mechanisms that bound the heavy metals to the biochar. It was found that biochar at 5% (BC5) and the mixture of biochar and apatite at 3% (BCA3) resulted in the greatest reduction of exchangeable forms of Cd, Pb and Zn. The increase in soil pH caused by adding biochar and apatite created more negative charge on the soil surface that promoted Pb, Zn and Cd adsorption. Heavy metals were mainly bound in the organic, Fe/Mn and carbonate fractions of the biochar and the mixture of biochar and apatite by either ion exchange, adsorption, dissolution/precipitation and through substitution of cations in large organic molecules